The Influence Of Charismatic Leadership And Work Environment On Employee Productivity With Work Discipline As A Mediating Variable In Regional Government Organizations Of Lahat Regency - Titi Hasanah; Markus Markus; Saparudin Saparudin (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This This study aims to examine the effect of charismatic leadership and work environment on employee productivity, with work discipline as a mediating variable, at Regional Government Organizations (OPD) of Lahat Regency. The respondents in this study consisted of 60 employees selected through purposive sampling. This research employed a quantitative approach, and data analysis was conducted using SmartPLS 3.0 software. The results indicate that charismatic leadership and work environment have positive and significant effects on employee productivity both directly and indirectly through work discipline as a mediating factor. Furthermore, work discipline was found to significantly mediate the relationship between charismatic leadership, work environment, and employee productivity.Based on the data analysis results, it can be concluded that charismatic leadership and work environment have a positive and significant direct effect on employee productivity at the Regional Government Organizations (OPD) of Lahat Regency. Furthermore, work discipline serves as a mediating variable that strengthens the relationship between charismatic leadership and work environment with employee productivity.